Emotions elicited by local food consumption, memories, place attachment and behavioural intentions. Issue 3 (3rd July 2017) - Sthapit, Erose; Björk, Peter; Coudounaris, Dafnis N.
Abstract: This study examines the influence of food consumption emotions on tourist's memories of a trip, place attachment, and behavioural intentions. A web-based post-holiday survey was conducted among tourists to Rovaniemi, Finland, and a valid sample of 241 tourists was used for data analysis. Structural equation modelling was applied and all the proposed hypotheses were supported. The findings demonstrate the role of food consumption emotions on the formation of memories that further influence behavioural intentions and place attachment. Memories also mediate in both of the relationships (i.e. between "food consumption emotions" and "place attachment" and between "food consumption emotions" and "behavioural intentions". The managerial implications include that restaurant managers should formulate a local food quality evaluation system and programme to enable tourists to gain sensual enjoyment. They should also ensure food safety to avoid negative feelings among tourists. Finally, they should focus on the servicescape and storytelling, as well as offer food souvenirs that appeal to tourists' emotions.